2010
DOI: 10.1007/s10517-010-0985-1
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Results of Transplantation of Fetal Neurogenic Tissue in Patients with Consequences of Spinal Cord Trauma

Abstract: We analyzed delayed effects of transplantation of nervous and hemopoietic fetal cells to patients with consequences of spinal trauma. A decrease in neurological deficit associated with pronounced improvement of functional independence was observed in 48.9% cases. The best results were observed in patients receiving cell transplantation within the first 2 years after trauma and in younger individuals. The pattern of morphological changes in the spinal cord at site of injury, severity of damage, and the method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…In clinical studies, transplantation of neural stem cells has been applied for human cases of severe SCI; however, the therapeutic effects of NSPC transplantation are still controversial ( Harrop et al., 2012 ). Seledtsova and colleagues transplanted human-derived NSPCs into the injured spinal cords of 43 patients, and nearly half of the patients (49%) showed some functional improvement after transplantation ( Seledtsova et al., 2010 ). Although Dobkin and colleagues also transplanted human-derived NSPCs into the injured spinal cords of seven patients, none of these patients achieved a functional recovery after transplantation ( Dobkin et al., 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, transplantation of neural stem cells has been applied for human cases of severe SCI; however, the therapeutic effects of NSPC transplantation are still controversial ( Harrop et al., 2012 ). Seledtsova and colleagues transplanted human-derived NSPCs into the injured spinal cords of 43 patients, and nearly half of the patients (49%) showed some functional improvement after transplantation ( Seledtsova et al., 2010 ). Although Dobkin and colleagues also transplanted human-derived NSPCs into the injured spinal cords of seven patients, none of these patients achieved a functional recovery after transplantation ( Dobkin et al., 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…These authors noted a correlation between neurological recovery and patient age, as the younger patients had a greater neurological improvement (67% of patients under 20 years of age improved vs 0% of those more than 50 years of age). 56 In addition, there was a greater FIM improvement in patients without intramedullary cysts (55%) than in those with a cyst (45%), which suggests that the surgical intervention and decompression of the syrinx and spinal tethering was not the origin of the neurological improvement.…”
Section: Fetal Neurogenic Tissue Transplantationmentioning
confidence: 91%
“…Nine of the 12 studies lacked a control population in their design, which resulted in a downgrading of the paper to a Grade IV. 14,23,32,35,41,46,52,56,62 There were no prospective randomized studies (Grade I or II). This lack of prospective randomization and control populations appears to be the result of several studies being performed as pilot or safety studies.…”
Section: Quality Of the Literature And Studiesmentioning
confidence: 99%
“…Rabinovich (2003), Moviglia (2006) and Seledtsova (2010) reported that transplantation of OEC or/and BMMC combination in patients with SCI, showed some functional recovery [41,73,74]. Moviglia (2006) reported that combined protocol of cell therapy for chronic SCI by intravenous (IV) and intra-arterial (IA) showed electrical and functional recovery [46].…”
Section: Different Cell Combinationmentioning
confidence: 99%